Comparative assessment of immunomodulatory, proliferative, and antioxidant activities of crocin and crocetin on mesenchymal stem cells. Issue 1 (20th September 2020) - Yousefi, Forouzan; Arab, Fahimeh L.; Rastin, Maryam; Tabasi, Nafiseh S.; Nikkhah, Karim; Mahmoudi, Mahmoud
Abstract: Saffron ( Crocus sativus L) is a well‐known spice with active pharmacologic components including crocin, crocetin, safranal, and picrocrocin. Similar to crocin/crocetin, mesenchymal stem cells (MSCs) have been shown to display immunomodulatory and antioxidant properties, which could be beneficial in treatment of various diseases. In the current study, we have evaluated the effects of crocin and crocetin on the functions of MSCs. We used the 3‐(4, 5‐dimethyl‐2‐thiazolyl)‐2, 5‐diphenyl‐2H‐tetrazolium bromide assay to evaluate MSCs proliferation, and flow cytometry assay to measure the percentage of apoptotic MSCs and Tregs populations. Furthermore, we used the real‐time polymerase chain reaction method to quantify messenger RNA (mRNA) expression of inflammatory and anti‐inflammatory cytokines. Antioxidant assay was employed to quantify antioxidant parameters including nitric oxide and malondialdehyde levels besides superoxide dismutase activity. Our findings indicated that both crocin and crocetin at low concentrations (2.5 and 5 µM) exhibited significant effects on increasing MSCs viability and on protecting them against apoptosis‐induced death. Furthermore, crocin and crocetin at low concentrations (2.5 and 5 µM) displayed a better antioxidant function. Moreover, increased Treg population was observed at lower doses. In addition, crocin/crocetin at low concentrations caused an elevation in mRNA expression of anti‐inflammatory cytokines (transforming growth factor‐β, interleukin‐10 [IL‐10], and IL‐4), while at higher doses (25 and 50 µM) they led to lowering inflammatory cytokines (IL‐1β, IL‐6, IL‐17, and interferon gamma). Altogether, both crocin and crocetin at lower concentrations exhibited more efficacies on MSCs with a better effect toward crocin. It seems that crocin and crocetin may be considered as complementary treatments for the patients who undergo MSCs transplantation. Abstract : Both crocin and mesenchymal stem cells (MSCs) have anti‐inflammatory, antioxidant, and cytoprotective effects. Combination of crocin and MSCs could exert a better effect on ameliorating of multiple sclerosis severity.